Device for initiating the SHS process - Luzan, S. A.; Sytnykov, P. A. (My University, 2023)
The structure and operating principle of a special device for initiating the SHS process are described. The device consists of a tripod with a sample placement table, a movable dielectric clamp with a glowing filament, and a power transformer.
Keywords: SHS-process; device; power transformer; spiral; composite material